2012
DOI: 10.1016/j.joep.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Slipping the surly bonds: The value of autonomy in self-employment

Abstract: This paper models the tradeo¤ between increased autonomy from self-employment and the generally higher income that traditional employment o¤ers. While the demand for autonomy is a purely psychological construct, the economic tradeo¤s involved in its achievement are eminently amenable to quanti…cation and analytical modeling characteristic of economic analysis. We use this setup to o¤er a multifactor utility formulation formalizing the notion of an explicit, autonomy-based preference for self-employment. We pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 48 publications
3
56
1
Order By: Relevance
“…Emotional attachment to the business refers to the value associated to the non financial benefit of owing the firm (Zellweger & Astrachan, 2008) and encompasses the desire of maintaining the control of a family business as a form of loyalty to the family (Madison, Runyan, & Swinney, 2014). The literature has also found that need-for-achievement and need-for-independence, individually considered, are positively associated with EO, while emotional attachment may be found in more conservative strategic postures (Brandst€ atter, 2011;Carter, Gartner, Shaver, & Gatewood, 2003;Croson & Minniti, 2012).…”
Section: Motivational and Personality Pathways To Eomentioning
confidence: 99%
“…Emotional attachment to the business refers to the value associated to the non financial benefit of owing the firm (Zellweger & Astrachan, 2008) and encompasses the desire of maintaining the control of a family business as a form of loyalty to the family (Madison, Runyan, & Swinney, 2014). The literature has also found that need-for-achievement and need-for-independence, individually considered, are positively associated with EO, while emotional attachment may be found in more conservative strategic postures (Brandst€ atter, 2011;Carter, Gartner, Shaver, & Gatewood, 2003;Croson & Minniti, 2012).…”
Section: Motivational and Personality Pathways To Eomentioning
confidence: 99%
“…Owner-managers tend to attach a high value to independence (β) (Croson and Minniti 2012) and exhibit comparatively higher levels of risk propensity (α) . Since risk propensity is also assumed to increase with age, these parameters suggest that, ceteris paribus, enterprising activity in this preference group should increase with age.…”
Section: Owner-managersmentioning
confidence: 99%
“…Self-employers are interested in maintaining a lifestyle and attach a comparatively high value to independence (β) (Croson and Minniti 2012). They are also 8 inclined to reduce exposure to risk.…”
Section: Self-employersmentioning
confidence: 99%
“…2 It seems thus natural to assume that there is a trade-off between these beneficial working conditions and earnings in self-employment that accounts for the apparently low returns to entrepreneurship. Croson & Minniti (2012) develop a theoretical model based on this idea that implies that the self-employed will in fact have (initially) lower earnings in exchange for more beneficial working conditions. Åstebro & Thompson (2011) also argue that entrepreneurs may be willing to forego earnings to satisfy a taste for variety.…”
Section: Introductionmentioning
confidence: 99%